2018
DOI: 10.1094/mpmi-07-17-0188-fi
|View full text |Cite
|
Sign up to set email alerts
|

The Agrobacterium F-Box Protein Effector VirF Destabilizes the Arabidopsis GLABROUS1 Enhancer/Binding Protein-Like Transcription Factor VFP4, a Transcriptional Activator of Defense Response Genes

Abstract: Agrobacterium-mediated genetic transformation not only represents a technology of choice to genetically manipulate plants, but it also serves as a model system to study mechanisms employed by invading pathogens to counter the myriad defenses mounted against them by the host cell. Here, we uncover a new layer of plant defenses that is targeted by A. tumefaciens to facilitate infection. We show that the Agrobacterium F-box effector VirF, which is exported into the host cell, recognizes an Arabidopsis transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…The transcript levels of the pathogen response marker genes PR1 and PR5 are increased in the mutant, indicating that the GeBP/GPLs are repressors of PR genes. A recent study revealed that VirF and its plant functional homolog VBF of the Agrobacterium F-box effector interact with the Arabidopsis GeBP-like transcription factor VFP4 [27]. Loss-of-function mutation of VFP4 results in the differential expression of numerous biotic stress response genes, suggesting that one of the functions of VFP4 is to control a spectrum of plant defenses, including against Agrobacterium tumefaciens.…”
Section: Introductionmentioning
confidence: 99%
“…The transcript levels of the pathogen response marker genes PR1 and PR5 are increased in the mutant, indicating that the GeBP/GPLs are repressors of PR genes. A recent study revealed that VirF and its plant functional homolog VBF of the Agrobacterium F-box effector interact with the Arabidopsis GeBP-like transcription factor VFP4 [27]. Loss-of-function mutation of VFP4 results in the differential expression of numerous biotic stress response genes, suggesting that one of the functions of VFP4 is to control a spectrum of plant defenses, including against Agrobacterium tumefaciens.…”
Section: Introductionmentioning
confidence: 99%
“…This complex may enable T-DNA integration by proteasomal degradation of VIP1 and VirE2 (Tzfira et al, 2004). In addition, it may destabilize VFP4, a transcriptional activator of defense response genes (Garc ıa-Cano et al, 2018). VBF, a plant F-box protein, might functionally replace VirF in plant species that do not require VirF for successful transformation (Zaltsman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The F-box protein activity of A6-VirF was demonstrated in yeast and in plant cells, and one of its potential substrates and interacting partners was identified; specifically, VirF was shown to bind VIP1 and destabilize via the ubiquitin–proteasome system (UPS) both VIP1 and its associated VirE2 (128). More recently, several other Arabidopsis interactors of VirF were identified (42, 43), one of which, VFP4, a transcriptional regulator of genes involved in stress or defense response, was targeted by VirF for proteasomal degradation (42). In addition, VirF itself is destabilized via UPS, and this destabilization is prevented by VirF interaction with another effector, VirD5 (82).…”
Section: Variability Of the Molecular Pathway For Agrobacterium Infecmentioning
confidence: 99%